Theoretical Study of Optical Field Distribution of TeO2 Modulator Diffraction - Jawad, Hind Jassim (Al-Nahrain Journal of Science, 2013)
In this paper, attention is focused on the analysis of the modulation transfer function form and its dependence on the normalized distance along the crystal (ξ) and peak phase delay (α). The numerical calculations show that the diffracted beam profile has very complicated waveform structure depending on both acoustic and optical parameters.